Transformational Leadership Style And Innovative Work Behavior: The Moderating Role Of Affective Commitment - Anggun Tiur Ida Sinaga; Benjamin Albert Simamora (CV Putra Publisher, 2026)
The problem of employee work behavior in public organizations is a classic problem that has been widely complained about by the public. This study tries to solve this problem by analyzing how transformational leadership influences innovative work behavior and how the moderating role of affective commitment improves innovative work behavior. Data were collected from 786 employees in local governments of districts/cities in the province of North Sumatra. Data were analyzed using structural equation modeling (SEM). The results showed that transformational leadership has a significant effect on innovative behavior, affective commitment has a significant effect on moderating the relationship between transformational leadership and innovative work behavior